Hydroxyapatite particles induced modulation of collagen expression and secretion in primary human dermal fibroblasts - Rakshit, Moumita (2021)
Background Hydroxyapatite (HA) [Ca5(PO4)3(OH)] is a naturally occurring calcium phosphate which makes up 60–70% of the dry weight of human bones. Nano-scale HA particles are increasingly being used as carriers for controlled and targeted delivery of bioactive agents like drugs, proteins, and nucleic acids due to their high porosity, negative charge, and biodegradability.